Collection and Characterization of Trait Specific Multi-crop Germplasm from Sikkim - Rathi, R. S.; Singh, S.K.; Misra, A.K. (Indian Journal of Hill Farming, 2019)
Considering the importance of agro-biodiversity of Sikkim, an exploration and collection tour was conducted for collection of maize, rice, buckwheat and Vigna spp germplasm from East, West and South districts of Sikkim. The altitude of explored area ranged between 612 to above 2900 msl. The local landraces and primitive crop germplasm were collected. It has been observed that the inhabitants practiced main agricultural in their permanent traditional fields followed by Jhum (Shifting) cultivation. The tribal and other farmingÂ ommunities in explored area are still using their traditional agriculture methods along with modern techniques. The local farmers have been growing their traditional landraces/cultivars since time immemorial either by saving their own seeds or by arranging seeds through barter or exchange system. Under this trip, 121 germplasm acces. of Zea mays, Oryza sativa, Fagopyrum esculentum, F. tataricum, Vigna umbellata, V. mungo, V. radiate, V. angularis and V. unguiculata were collected. Additionally, local indigenous traditional information practiced by the farmers was also recorded. Collected germplasm were characterized at experimental farm of ICAR-NBPGR Regional Station, Umiam, Meghalaya. Extents of diversity within the collected crop germplasm have been summarized in this study.